Giant juvenile fibroadenoma of the breast: a case report - Moukit, Mounir; Rahmoune, Mohammed; Allilou, Ismail; Babahabib, Abdellah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Giant juvenile fibroadenoma is a rare benign breast entity. The clinical presentation can be dramatic mimicking malignancy. Meticulous surgical management is mandatory to ensure a fine balance between adequate tumor resection and the best cosmetic outcome for the mammary gland. We report a case of a 13-year-old girl who presented to our department with a 20×18 cm mass on her left breast. Imaging and histopathological investigations were suggestive of juvenile fibroadenoma. Conservative surgery was performed with good cosmetic results. Giant fibroadenoma must be considered in any adolescent female with a rapidly growing breast mass. Simple surgical excision is recommended to allow normal breast tissue to grow.